Answer:
![\huge\boxed{\sf Right.}](https://tex.z-dn.net/?f=%5Chuge%5Cboxed%7B%5Csf%20Right.%7D)
Step-by-step explanation:
![(-a+b)^2](https://tex.z-dn.net/?f=%28-a%2Bb%29%5E2)
Let's apply the formula (x+y)² = x² + 2xy + y²
Here, x = -a and y = b
So,
= (-a)² + 2(-a)(b) + (b)²
= a² - 2ab + b²
Hence, it has been proved that (-a + b)² = a² - 2ab + b².
![\rule[225]{225}{2}](https://tex.z-dn.net/?f=%5Crule%5B225%5D%7B225%7D%7B2%7D)
Hope this helped!
<h3>~AH1807</h3>
Answer:
Step-by-step explanation:
1.) Apply the distributive law
5x + 5 * 2
2.) Multiply the numbers
5 * 2 = 10 is equivalent to 5x + 10
3.) Group like terms
5x - 3 + 10
4.) Add/subtract the numbers
-3 + 10 = 7 is equivalent to 5x + 7
Answer:
slope=4
Step-by-step explanation:
m=y2-y1/x2-x1
4-(-4)=8
5-3=2
8/2=4
hope this helps :3
if it did pls mark brainliest